2005
DOI: 10.1139/b04-146
|View full text |Cite
|
Sign up to set email alerts
|

The concentrations and distribution of phytic acid-phosphorus and other mineral nutrients in wild-type andlow phytic acid1-1 (lpa1-1) corn (Zea maysL.) grains and grain parts

Abstract: A comparison of mineral nutrient and phytic acid-phosphorus (PA-P) distribution in the grains of wild-type (WT) and low phytic acid1-1 (lpa1-1) corn (Zea mays L.) was conducted to determine how the lpa1-1 mutation influences mineral element concentrations in different grain parts and impacts the structure of phosphorus-rich inclusions (globoids) in the grain cells. This is the first report regarding total phosphorus (P) and PA-P concentrations in scutellum and root-shoot axis portions of cereal embryos of WT i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 29 publications
5
60
1
2
Order By: Relevance
“…However, in these studies, Cu and Zn may have had a high affinity for InsP 6 . In contrast to these in vitro results, in vivo InsP 6 is stored mainly with Mg and K in rice and corn (Zea mays) seeds (Ogawa et al, 1975;Lin et al, 2005) and with Mg, K, and Ca in wheat (Triticum aestivum) seeds (Bohn et al, 2007). In this study, m-XRF analysis at a 1-mm step size also indicated that Ca, K, and Fe bind strongly to phytic acid, Zn binds loosely, and Cu scarcely binds to phytic acid.…”
Section: Discussioncontrasting
confidence: 80%
“…However, in these studies, Cu and Zn may have had a high affinity for InsP 6 . In contrast to these in vitro results, in vivo InsP 6 is stored mainly with Mg and K in rice and corn (Zea mays) seeds (Ogawa et al, 1975;Lin et al, 2005) and with Mg, K, and Ca in wheat (Triticum aestivum) seeds (Bohn et al, 2007). In this study, m-XRF analysis at a 1-mm step size also indicated that Ca, K, and Fe bind strongly to phytic acid, Zn binds loosely, and Cu scarcely binds to phytic acid.…”
Section: Discussioncontrasting
confidence: 80%
“…During seed development, the aleurone cells are gradually filled with globoids and oil bodies, and therefore, metal elements that do not form phytate salt will be gradually extruded from the aleurone layer to the endosperm. A reduction in globoid size was observed in the aleurone layer of lpa seeds in rice, barley, and corn [32,35,36]. Because the estimated width of the aleurone layers of the two lpa mutants were similar to that of WT, it is plausible that Zn and Cu in the lpa seeds were not moved out into the endosperm, but remained in the spaces between small globoids in the aleurone layer.…”
Section: Discussionmentioning
confidence: 99%
“…Results obtained for maize (Lin et al, 2005), barley (Liu et al, 2007a) and wheat (Guttieri et al, 2006) indicated that lpa mutations do not result in systematic increases or decreases of the mineral contents in these crops.…”
Section: Introductionmentioning
confidence: 91%